Problematika Ketaatan Siswa Kelas X IIS 2 Dalam Menjalankan Ibadah Salat Fardu - Filza Syadi; Al Ikhlas (Prodi Pendidikan Keagamaan Islam, 2022)
This study aims to find out how students' obedience in carrying out fardu prayer services, problems with student obedience in carrying out fardu prayers, and the efforts of Islamic religious education teachers on student obedience in carrying out fardu prayer services. This research uses qualitative methods with a descriptive approach. The data source was obtained from 25 students of class X IIS 2 at SMA Negeri 01 Sungai Geringging through a research questionnaire and three informants, namely two Islamic religious education teachers and one homeroom teacher from class X IIS 2. Overall, the results of the analysis showed that the adherence of class X IIS 2 students in carrying out fardu prayers at SMA Negeri 01 Sungai Geringging was quite good with a percentage of 64%. Factors that affect the obedience of class X IIS 2 students in carrying out fardu prayer services at SMA Negeri 01 Sungai Geringging include internal and external factors. The problems of student prayers are inadequate facilities and infrastructure for prayer services, lack of understanding of student prayer services, and students' busyness with worldly affairs. The efforts of PAI teachers towards the obedience of class X IIS 2 students in carrying out fardu prayers at sma negeri 01 Sungai Geringging are to provide motivation, provide an Islamic spiritual forum (Rohis), provide value as a form of reward and sanctions and make a schedule for the implementation of congregational prayers in schools.